Juggling Paperwork Across Borders: Theorizing Transnational Legal Space - Betty de Hart (Nordic Journal of Migration Research)
Life events such as marriage, divorce or the birth of children are not just intimate family matters but also legal matters. For transnational families, such life events are influenced by multiple overlapping nation-state orders, each with its own set of laws and institutions. This contribution builds on the concept of transnational legal space to study the social workings of law across borders from a bottom-up perspective of transnational family members’ lives. Linking two strands of literature – the literature on transnational legal space and that on transnational social space – it moves away from more top-down approaches centring on transnational processes of legal norm-making and, instead, uses a bottom-up approach focusing on family members who mobilize law in transnational social space and who thus create and apply new norms in response to the interaction – or, at times, collision – of different legal systems. The usefulness of this approach is illustrated by empirical evidence from two research projects on family law and dual citizenship. It contributes to research on transnational migration by demonstrating that, in transnational legal space, it is not the law that is transnational, given that the nation-state and national laws continue to remain highly relevant, and similarly that it is not just mobility and migration regimes but also a variety of different areas of law that impact the everyday lives of transnational families. How these families navigate transnational legal space differs, depending on the intersection of race, gender and class.